Land surveying and geodetic sectors of Ukraine during wartime: transformations and challenges - Martyn, A.; Bavrovska, N. (Land Management, Cadastre and Land Monitoring, 2024)
This article is dedicated to the current state of the land surveying and geodetic sectors in Ukraine, particularly in the context of the impact of the COVID-19 pandemic and Russian military aggression. The authors emphasize the critical role of these sectors in ensuring land and property rights, spatial planning, land resource management, and providing technological and environmental safety. The article examines the main transformations, challenges, and opportunities for the professional activities of land surveyors and geodesists during wartime, as well as their role in the post-war reconstruction of the country. Specifically, a detailed analysis of the certification dynamics of land surveyors and geodesists for the period of 2013–2024 has been conducted, allowing for an assessment of the sector considering both economic and social challenges. The increase or decrease in the number of newly certified specialists enables the evaluation of labor market activity and the impact of crisis factors on the sector's operations. The study also explores regional employment peculiarities, analyzing dynamics in front-line, de-occupied, rear, and support regions. The article highlights the significant role of gender balance in engineering professions, particularly noting the increasing access of women to technical specialties previously considered predominantly male. Analysis of gender ratios demonstrates progress in ensuring equal opportunities for both genders in the land surveying and geodetic fields. The main conclusions of the study indicate that the land surveying and geodetic sectors require the integration of the latest technologies, such as Geographic Information Systems (GIS) and remote sensing, to enhance their efficiency during wartime and post-war recovery. The use of unmanned aerial vehicles for geodata collection in hazardous regions and the adaptation of educational programs to train new specialists considering new realities are key development directions for the sector. The article is an important contribution to understanding the current challenges and opportunities for the land surveying and geodetic sectors during wartime, providing scientific and practical recommendations for strategic development.Keywords: land surveying sector, geodetic sector, certified engineers, Geographic Information Systems (GIS), remote sensing, wartime, post-war reconstruction, gender balance, labor market, spatial planning.
Keywords: land surveying sector; geodetic sector; certified engineers; Geographic Information Systems (GIS); remote sensing; wartime; post-war reconstruction; gender balance; labor market; spatial planning